Deep Infiltrative Endometriosis: A Review of Surgical Treatment Options - Corina Adelina Zah; Paul Grama; Octavian Andronic; Romina Sima (Al Ameen Medical College, 2021)
Deep infiltrative endometriosis (DIE) is defined as the presence of ectopic endometrial mucosa that infiltrates more than 5 mm of the peritoneum, in most cases accompanied by pain. Surgery is the treatment of choice in most cases. The aim of this review is to present the variety of surgical approaches to DIE. We performed a thorough MEDLINE search using the terms "(surgery OR surgical treatment OR surgical procedures OR surgical approach OR surgical technique) AND (deeply infiltra* endometriosis OR deep endometriosis OR infiltrative endometriosis). A total of 17 articles were included in the present study. Depending on the site of the lesion, different surgical techniques can be used. Laparoscopy is the most used approach for different lesion sites. It can be combined with open surgery if needed. Another promising alternative to laparoscopy is robotic surgery. For lesions that are not very extensive ablation and shaving techniques can be performed.